A Dermocosmetic Significantly Reduces the Frequency and Intensity of Facial Skin Intolerability and Sensitivity in Subjects with Skin Intolerant to Skin Care Products and Sensitive Skin - Kerob D; Czermanska A; Karamon EM; Moga A; Lecerf G; Nioré M; Le Dantec G; Le Floc'h C; Tan J (Dove Medical Press, 2023)
Delphine Kerob,1 Anna Czermanska,2 Ewa M Karamon,3 Alain Moga,4 Guillaume Lecerf,4 Margot Nioré,1 Guénaëlle Le Dantec,1 Caroline Le Floc'h,1 Jerry Tan5 1Scientific Direction, La Roche-Posay Laboratoire Dermatologique, Levallois-Perret, France; 2Dermascan, Poland Sp. z o. o., Gdansk, Poland; 3Studio Dermatologia i Kosmetyka ul, Malbork, Poland; 4QIMA Bioalternatives - Prologue Biotech, Labège, France; 5Western University, Department of Medicine and Windsor Clinical Research Inc, Windsor, ON, CanadaCorrespondence: Delphine Kerob, Scientific Direction, La Roche-Posay Laboratoire Dermatologique, International Scientific Affairs, Levallois-Perret, France, Email delphine.kerob@loreal.comIntroduction: Intolerance to dermocosmetics is frequent in subjects with allergic contact dermatitis (ACD). A dermocosmetic (DC) was developed to restore the natural skin barrier, to reduce skin inflammation and to improve sensitive skin in ACD.Objective: To assess the benefit of a DC in subjects with an allergic background and intolerance to cosmetic care, or with sensitive skin.Materials and Methods: In this open-label study, 107 subjects above 16 years of age applied DC on the face twice a day for 28 days. Assessments at Days 0, 14 and 28, included skin sensitivity, stinging test, local tolerance, transepidermal water loss (TEWL), skin hydration, inflammatory biomarkers (IL-1α, IL-1RA, PGE2) using tape stripping and subject satisfaction.Results: 88% were women and mean age was 42.0± 15.0 years. Skin sensitivity at inclusion scored 5.9± 0.35; 46% had ACD, 95% skin irritation, 92% sensitive skin and 88% intolerance to cosmetics. A significant (p< 0.0001) 85% decrease of frequency and intensity of the composite score was observed at both endpoints. Stinging scores significantly (p< 0.0001) decreased from 3.9 at baseline to 2.4 at Day 14 and 1.4 at Day 28; 77% and 81% of subjects reported improved skin reactivity at Day 14 and Day 28, respectively. Similar improvements were noted in the frequency and intensity of irritation, erythema, stinging, burning and discomfort. TEWL, skin hydration and inflammatory biomarker levels significantly (p< 0.0001) improved. Overall subject satisfaction (85%) and tolerance (investigators: 99%, subjects: 97%) were high.Conclusion: DC significantly reduced the frequency and intensity of facial skin intolerability and sensitivity in subjects with skin intolerant to skin care products.Clinicaltrials.gov Identifier: NCT05487937.Keywords: dermocosmetic, allergic prone skin, sensitive skin